Crime and immigration: New evidence from England and Wales - Laura Jaitman; Stephen Machin (IZA Journal of Migration, 2013)
We study a high profile public policy question on immigration, namely the link between crime and immigration, presenting new evidence from England and Wales in the 2000s. For studying immigration impacts, this period is of considerable interest as the composition of migration to the UK altered dramatically with the accession of Eastern European countries (the A8) to the European Union in 2004. As we show, this has important implications for ensuring a causal impact of immigration can be identified. When we are able to implement a credible research design with statistical power, we find no evidence of an average causal impact of immigration on crime, nor do we when we consider A8 and Non-A8 immigration separately. We also study London by itself as the immigration changes over time in the capital city were large. Again, we find no causal impact of immigration on crime from our spatial econometric analysis and also present evidence from unique data on arrests of natives and immigrants in London which shows no immigrant differences in the likelihood of being arrested.
Keywords: F22; K42; 330; Crime; Immigration; Enclaves; A8